Supercapacitors: A new source of power for electric cars? - Horn, Michael; MacLeod, Jennifer; Liu, Meinan; Webb, Jeremy; Motta, Nunzio (Economic analysis and policy, 2019)
Supercapacitors are electric storage devices which can be recharged very quickly and release a large amount of power. In the automotive market they cannot yet compete with Li-ion batteries in terms of energy content, but their capacity is improving every year. They are already used as ancillary devices to store energy from braking and to provide the necessary boost during quick accelerations, ultimately increasing the efficiency of the vehicle. This paper will introduce the basic physics of supercapacitors and provide a brief review of state-of-the art of materials, technological advances and applications, with an eye to their future usage in cars should the present trends in electrical storage continue. [Display omitted]